2019
DOI: 10.1186/s12936-019-2877-9
|View full text |Cite
|
Sign up to set email alerts
|

“We were afraid of the lion that has roared next to us”; community response to reactive focal mass drug administration for malaria in Eswatini (formerly Swaziland)

Abstract: Background Reactive focal mass drug administration (rfMDA), or presumptive treatment without malaria testing of household members and neighbours of a passively identified malaria case, is currently being explored as a possible malaria elimination strategy in low transmission settings. One of the primary factors determining the effectiveness of rfMDA on reducing or interrupting transmission is achieving high coverage of the target population with drug administration. This study aims to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…High coverage and acceptability could have been due to effective community sensitisation activities before the study, 10 ongoing engagement by staff during pharmacovigilance and follow-up visits, and high motivation for individuals to participate because of the perceived threat of malaria when there was a recent case in their neighbourhood. 34 Our study has some limitations. First, the large differences in crude and adjusted incidence and prevalence estimates were due to an imbalance of factors in the study arms that were associated with the trial outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…High coverage and acceptability could have been due to effective community sensitisation activities before the study, 10 ongoing engagement by staff during pharmacovigilance and follow-up visits, and high motivation for individuals to participate because of the perceived threat of malaria when there was a recent case in their neighbourhood. 34 Our study has some limitations. First, the large differences in crude and adjusted incidence and prevalence estimates were due to an imbalance of factors in the study arms that were associated with the trial outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…Adherence to presumptive treatment with DP was high, and as reported elsewhere, acceptability was high. (18) Importantly, there were no serious adverse events (SAEs).…”
Section: Discussionmentioning
confidence: 97%
“…The primary outcome of the trial was the cumulative incidence of malaria cases by study cluster over two-years of follow-up. Secondary outcomes reported here include safety and adherence (acceptability has been reported elsewhere(18)). Infection prevalence and seroprevalence at two-year follow-up were originally also secondary outcomes but the endline cross-sectional survey was not conducted due to a shift in priorities within the Ministry of Health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have evaluated the effect of adding reactive targeted interventions, including IRS and drug administration, to routine population-wide measures, to further reduce or eliminate malaria. 13 , 14 , 45 , 46 , 47 A trial in Namibia showed effective reduction of malaria incidence through reactive focal mass drug administration and reactive focal IRS, alone and in combination, when added to standard IRS. 14 Our trial is unique in using a non-inferiority design to assess whether replacing annual IRS campaigns with reactive IRS targeting at-risk neighbourhoods would be safe and prevent malaria from surging out of control.…”
Section: Discussionmentioning
confidence: 99%